Herbivore-induced volatile emissions from cotton (Gossypium-hirsutum L) seedlings - McCall, Philip J; Turlings, Ted; Loughrin, John H; Proveaux, Adron T; Tumlinson, James H (My University, 1994)
The effect of herbivory on the composition of the volatile blends released by cotton seedlings was investigated by collecting volatiles from undamaged, freshly damaged (0-2 hr after initiation of feeding), and old damaged (16-19 hr after initiation of feeding) plants on which com earworm caterpillars (Helicoverpa zea Boddie) were actively feeding. A blend of 22 compounds was consistently observed to be emitted by the old damaged plants with nine occurring either only in, or in significantly greater amounts in old damaged, as compared with freshly damaged plants. These were (Z)-3-hexenyl acetate, hexyl acetate, (E)-beta-ocimene, (3E)-4,8-dimethyl-1,3,7-nonatriene, (Z)-3-hexenyl butyrate, (E)-2-hexenyl butyrate, (Z)-3-hexenyl 2-methylbutyrate, (E)-2-hexenyl 2-methylbutyrate, and indole, The nature of this response is compared with other studies where herbivore-induced volatile responses are also known. The presence of large amounts of terpenes and aldehydes seen at the onset of feeding and the appearance of other compounds hours later suggest that cotton defense mechanisms may consist of a constitutive repertoire that is augmented by an induced mechanism mobilized in response to attack. A number of the induced compounds are common to many plants where, in addition to an immediate defensive function, they are known to be involved in the attraction of natural enemies.
Keywords: COTTON; HELIOTHIS-ZEA; FEEDING DETERRENCE; PHYTOALEXIN; SEMIOCHEMICALS; TERPENES; TRITROPHIC INTERACTIONS; PARASITOID CAMPOLETIS-SONORENSIS; PREDATOR-PREY INTERACTIONS; LEAF-DERIVED VOLATILES; PLANT VOLATILES; HOST-PLANT; COTESIA-MARGINIVENTRIS; ASPERGILLUS-FLAVUS; CHEMICAL SIGNALS; IDENTIFICATION; ALLELOCHEMICALS